Universal Scaling Law for the Size Effect on Superelasticity at the Nanoscale Promotes the Use of Shape-Memory Alloys in Stretchable Devices - Fuster, Valeria de Los Angeles (2020)
Shape-memory alloys (SMAs) are the most stretchable metallic materials thanks to their superelastic behavior associated with the stress-induced martensitic transformation. This property makes SMAs of potential interest for flexible and wearable electronic technologies, provided that their properties will be retained at small scale. Nanocompression experiments on Cu-Al-Be SMA single crystals demonstrate that micro- and nanopillars, between 2 µm and 260 nm in diameter, exhibit a reproducible superelastic behavior fully recoverable up to 8% strain, even at the nanoscale. Additionally, these micro-/nanopillars exhibit a size effect on the critical stress for superelasticity, which dramatically increases for pillars smaller than ≈1 µm in diameter, scaling with a power law of exponent n = −2. The observed size effect agrees with a theoretical model of homogeneous nucleation of martensite at small scale and the universality of this scaling power law for Cu-based SMAs is proposed. These results open new directions for using SMAs as stretchable conductors and actuating devices in flexible and wearable technologies.